THE STRUGGLE IN NEGOTIATING CULTURAL IDENTITY IN LEILA SLIMANI'S THE COUNTRY OF OTHERS - Norlaili, Maulida; Istiani, Imas (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Identity is strongly related to one’s culture. When a person is in an estranged culture, he/she may find it difficult to adapt. This research aims to explain the main character Mathilde's struggle with cultural differences in Morocco and how she negotiates with cultural identity. The research is a literary criticism since the object of the research is a novel entitled The Country of Others written by a Moroccan novelist, Leila Sliman. This research views the literary text using the perspective of cultural identity theory by Stuart Hall. The findings show that there were cultural differences, norms, and stereotypes between Mathilde and Moroccan people, making her shocked by this situation. This causes rejection or denial and confusion of her cultural identity. The situation made her perceive herself as ‘other’ due to the difficulties she faced in accepting the new culture. Even though she initially had difficulties adapting to the new environment, in the end, Mathilde negotiated differences in cultural identity by harmonizing her new and old cultures in her new life in Morocco. It is hoped that in the future, this research can become a reference for research which uses other literary theories or studies on the same novel from different perspectives.